Optimized routing algorithm for mobile multicast source in wireless mesh networks - Sanni, M. L. (Institute of Electrical and Electronics Engineers Inc., 2016)
Mobility considerations in multicast algorithm design usually focus issues of mobile receivers while few researches emphasize on mobile multicast sources issues. However, mobility of source is a critical issue causing global tree disruption. Furthermore, major research challenges in the delivery of group applications over Wireless Mesh Networks (WMN) comprise delivery of large volume data, incurring large bandwidth and delay. This is in addition to multicast source mobility issues and interfering nature of scarce wireless resources. Mobile multicast scenarios emerge in group-based distribution of information such as obtains in the health sector, disaster recovery operation, remote bus, train control and video surveillance. The mobile multicast problem in this paper is formulated as a bandwidth and delay constrained minimum tree cost problem which is proved to be computationally intensive. Thus this paper proposes a Differential Evolution based optimized mobile multicast routing algorithm for the shared tree architecture. The proposed algorithm is implemented using MATLAB and the evaluation considers analytic and simulation techniques for convergence, scalability and multicast tree stability under source movement. Simulation results show that the proposed algorithm converges and outperforms a source based tree algorithm.